Analyzing the Effect of Wind Flow at Openings, Wall Density and Distance of Livestock Cages on the Spread of Malaria Mosquitoes Using Ecotect Simulation - Hildegardis, Cornelia; Elfi, Teresia; Marsela, Theresia (Journal La Multiapp, 2025)
The government has set a target for Indonesia to become malaria-free; However, this goal has not yet been fully achieved, particularly in eastern regions such as Sikka Regency in East Nusa Tenggara. One of the factors contributing to the spread of malaria-carrying mosquitoes is the proximity of openings, wall density, and the distance of livestock enclosures from residential buildings, especially when less than 1 meter apart. Based on this, field observations were conducted in malaria-affected locations. These observations were followed by experiments using *Ecotect Analysis* to analyze wind patterns and velocities by comparing the distance between openings, wall density, and the distance of livestock enclosures at 1 meter and more than 5 meters. The study revealed that while distance does not influence wind velocity, it significantly affects wind flow patterns. Greater distances between openings result in broader air circulation patterns, which, in turn, impact the spread of mosquitoes in the area.